STRATEGI MASYARAKAT MULTIKULTURAL DALAM MEMBANGUN SOLIDARITAS (STUDI KASUS: ETNIS JAWA, BATAK DAN MINANG DI DESA SIPORA JAYA KECAMATAN SIPORA KABUPATEN KEPULAUAN MENTAWAI) - Setyawati, Gita Hermi; Fitlayeni, Rinel; Firdaus, Firdaus (Pendidikan Sosiologi, 2013)
Sipora Jaya people are people who have multicultur that consist of some etnich, where each etnic has different culture value. Although, Sipora Jaya people have many land of etnics but in Sipora Jaya village the conflic. Never happend between them, in this reseacher will discuss about how the strategy of multicultural people in Sipora Jaya village on building and creating solidarity between people there. Theory that used is solidarity social theory according to Emile Durkheim. Research method that used is case study bay kualitative approach. The instrument date is direct interview and observaion. This research did by asking 25 informan, that consist of three different etnics, they one Java, Batak, and Minang that the information were cellected by ceveral questions. As the result of this research, it show several supporting factor. How people build the solidarity, they are 1). Individual factor, 2). Environment factor, 3). Religion, 4). Force factor. From thore factors, three is a strategy that used by people of Sipora Jaya to build the solidarity. It is a activity that it doing together to create a cooperation and organizations that it be on unity between them. Type of strategy that used to avaid conflic are : 1). Cooperaticn in group of people. 2). Trust each other. 3). Respecting the norm in sacral environment. 4). Social acticity. 5). Work together.